Education in the 'right' sense of the word: The quest for a balanced education at the Kansas State Agricultural College - Halpin, Colin T. (Kansas State University. K-State Libraries, 2015)
After the establishment of the Kansas State Agriculture College in accordance with the Morrill Act, there was significant disapproval for the scope of education at the school, in favor of a more "practical" agricultural education which came under the leadership of President Anderson. Although Anderson made significant efforts in advancing education, his moves were too radical, and the final direction of the college was determined when President George Fairchild successfully combined the practical and classical structures to provide a broad curriculum that did not ignore the importance of hands-on training, and in doing so, he built a model agricultural college for the nation.
Citation: Halpin, C. T. (2014). Education in the 'right' sense of the word: The quest for a balanced education at the Kansas State Agricultural College. Unpublished manuscript, Kansas State University, Manhattan, KS.Kirmser Undergraduate Research Award - Individual Non-Freshman category, grand prize
Keywords: Kansas State Agricultural College; President George Fairchild; Education; Reform